Sundanese Sīrah in Indonesia Archipelago: A Contribution of R.A.A. Wiranatakoesoema’s Riwajat Kangdjeng Nabi Moehammad s.a.w. - Jajang A Rohmana (Al-Albab, 2017)
The article aims to analyze the influence of Sundanese culture in a book of sīrah or biography of Muhammad. This study focuses on R.A.A. Wiranatakoesoema’s Riwajat Kangdjeng Nabi Moehammad s.a.w. (1941), analyzed using hermeneutics. It is a Sundanese translation of Dinet and Sliman’s The Life of Mohammad (1918) which inserted twenty-seven French realist painting illustrations. Wiranatakoesoema did not only translate the book into Sundanese, but also added the great narratives in the form of Sundanese metrical poetry or dangding. The life of Muhammad was described into a Sundanese character like the personality of Sundanese noble. This research shows that Sundanese culture held great influence on Wiranatakoesoema’s narration of Muhammad’s life. Wiranatakoesoema’s Riwajat reflects the influence of Sundanese culture which represents the author as a Sundanese people. It is one of contributions of Sundanese culture and literature in narrating the same story of sīrah in various language of the world.